On the nomenclatural status of some species of Haplotaxidae (Clitellata) from Guinea - Martin, Patrick; Omodeo, Pietro; Rota, Emilia (Zootaxa, 2021)
Our attention was recently drawn to a problem of homonymy with Villiersia d’Orbigny, 1837, a nudibranch genus, posed by Villiersia Omodeo, 1987, an oligochaete genus of the family Haplotaxidae described from the Segea cave near Kindia, Guinea (Omodeo 1987). Examination of this case of homonymy has revived an old nomenclatural issue that dates back to 1958 when several taxa of the family Haplotaxidae were first proposed in a work on the oligochaete fauna of Mount Nimba (West Africa) (Omodeo 1958). A re-examination of the nomenclatural history of these taxa shows that subsequent nomenclatural interpretations made by some were unjustified, leading to a confusing situation. The taxa concerned, as currently accepted (Reynolds & Wetzel 2020), are the following: